2013
DOI: 10.1002/jat.2888
|View full text |Cite
|
Sign up to set email alerts
|

Ketamine attenuates cytochrome p450 aromatase gene expression and estradiol‐17β levels in zebrafish early life stages

Abstract: Ketamine, a dissociative anesthetic, is a noncompetitive antagonist of N-methyl-D-aspartate-type glutamate receptors. In rodents and non-human primates as well as in zebrafish embryos, ketamine has been shown to be neurotoxic. In cyclic female rats, ketamine has been shown to decrease serum estradiol-17β(E2) levels. E2 plays critical roles in neurodevelopment and neuroprotection. Cytochrome p450 (CYP) aromatase catalyzes E2 synthesis from androgens. Although ketamine down-regulates a number of CYP enzymes in r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 85 publications
(104 reference statements)
1
39
0
Order By: Relevance
“…These results indicated that the neurotoxicity of ketamine might be related to reduced endogenous 17β-estradiol secretion. Trickler et al (2013) recently reported that ketamine attenuates cytochrome p450 aromatase gene expression and 17β-estradiol levels in the early life stages of zebrafish , and ketamine has been shown to be neurotoxic to zebrafish embryos (Kanungo et al, 2013). Significant evidence points towards a trophic effect of endogenous 17β-estradiol in the developing brain during brain development.…”
Section: Discussionmentioning
confidence: 98%
“…These results indicated that the neurotoxicity of ketamine might be related to reduced endogenous 17β-estradiol secretion. Trickler et al (2013) recently reported that ketamine attenuates cytochrome p450 aromatase gene expression and 17β-estradiol levels in the early life stages of zebrafish , and ketamine has been shown to be neurotoxic to zebrafish embryos (Kanungo et al, 2013). Significant evidence points towards a trophic effect of endogenous 17β-estradiol in the developing brain during brain development.…”
Section: Discussionmentioning
confidence: 98%
“…These data are concordant with the results in multiple reports (cited above) on mammalian studies (neurotoxicity induced by ketamine in rodents and monkeys). Based on our continuing studies showing ketamine accumulation in 72 hpf embryos (48 hpf embryos exposed for 24 h to 2 mM ketamine) is much less (~7 μM/ embryo) compared to the 2.0 mM treatment dose (Trickler et al, 2013), we tested whether a similar phenomenon occurred in 28 hpf embryos that were treated for 20 h with 2.0 mM ketamine. The rationale behind this experiment was based on the notion that being younger by 20 h than the 48 hpf embryos, the skin of the 28 hpf embryos will be less complex and more permeable to ketamine, thus facilitating enhanced diffusion.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, zebrafish embryos/larvae are suitable alternatives since they are considered less susceptible to distress and pain than adults [27]. More important, zebrafish embryos/larvae express endocrine markers such as aromatase and vitellogenin that are affected by endocrine compounds, allowing them to be tested by monitoring the transcriptome [31,32]. Therefore, zebrafish embryos/larvae were employed to investigate the endocrine disruption of NAs in vivo in this study.…”
Section: Discussionmentioning
confidence: 98%
“…The zebrafish embryo/larvae has become a systematic, sensitive and easily operated mode animal for identify endocrine disruption [27]. Several zebrafish genes, such as CYP19a, CYP19b, ER␣, and VTG are wellknown biomarker genes responsive to environmental endocrine disruptors [28][29][30][31][32]. Therefore, a combined in vitro and in vivo approach is an efficient way to gain a complete understanding of the properties of endocrine disruptors.…”
Section: Introductionmentioning
confidence: 99%